2021
DOI: 10.3390/foods10040835
|View full text |Cite
|
Sign up to set email alerts
|

Gut Flora-Mediated Metabolic Health, the Risk Produced by Dietary Exposure to Acetamiprid and Tebuconazole

Abstract: The low-level and long-term exposure of pesticides was found to induce metabolic syndrome to mice. Metabolic pathways and mechanisms were investigated by detecting gut flora with metabolites, host circulation, and their interrelations. Results showed that the abundances of flora species and their metabolism were altered, consequently leading to metabolic disorders. A correlation analysis between gut flora and their metabolic profiling further explained these changes and associations. The metabolic profiling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In vertebrates, Romboutsia (among other bacteria) has been described as a key genus mediating physiological responses to agrochemicals. Liu et al [ 100 ] observed changes in the abundance of Romboutsia in mice exposed to fungicides and highlighted how this genus is involved in metabolic pathways such as the production of amino acids, free fatty acids and their methyl esters, phospholipids, nucleotides, carbohydrates and hormones. Similarly, Yang et al [ 101 ] described relationships between the abundance of Romboutsia and exposure to Deltamethrin, a commonly used pesticide in the Morogoro area.…”
Section: Discussionmentioning
confidence: 99%
“…In vertebrates, Romboutsia (among other bacteria) has been described as a key genus mediating physiological responses to agrochemicals. Liu et al [ 100 ] observed changes in the abundance of Romboutsia in mice exposed to fungicides and highlighted how this genus is involved in metabolic pathways such as the production of amino acids, free fatty acids and their methyl esters, phospholipids, nucleotides, carbohydrates and hormones. Similarly, Yang et al [ 101 ] described relationships between the abundance of Romboutsia and exposure to Deltamethrin, a commonly used pesticide in the Morogoro area.…”
Section: Discussionmentioning
confidence: 99%
“…La Merrill et al [74] demonstrated that perinatal exposure to DDT increased adiposity in young adult rats, reduced energy expenditure, and induced insulin resistance, which may be a result of impaired thermogenesis in exposed animals. In addition, recent studies have shown that pesticides can cause weight gain in rats chronically treated with low doses of pesticides and that this weight gain is also associated with changes in the gut microbiota of exposed animals [75,76].…”
Section: Biometric Assaymentioning
confidence: 99%
“…The control effect is more than 90%, it is compatible with the environment, and the shelf life is about 20 days. 1 Acetamiprid has biologically toxic effects on the human body; [2][3][4] it can enter food and human tissue during daily routines, stimulate neurotoxicity caused by acetylcholine receptors, penetrate human peripheral blood lymphocytes, and cause DNA damage. 5,6 Acetamiprid acts as an agonist of nicotinic acetylcholine receptors on neuronal postsynaptic membranes and it inhibits normal conduction in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%